The impact of a hospital electronic prescribing and medication administration system on medication administration safety: an observational study - Jheeta,S; Franklin,BD (BMC Health Services Research, 2017)
BackgroundThe aim of the study was to explore the impact of the implementation of an electronic prescribing and medication administration system (ePA) on the safety of medication administration in an inpatient hospital setting. Objectives were to compare the prevalence and types of: 1) medication administration errors, and 2) documentation discrepancies, between a paper and an ePA system. Additionally, we wanted to describe any observed changes to medication administration practices.MethodsThe study was based on an elderly medicine ward in an English hospital. From December 2014 to June 2015, nurses’ medication administration rounds were observed every 5 days before and after ePA implementation using an interrupted time-series approach. Medication administration error and documentation discrepancy rates pre- versus post-ePA were analysed descriptively and chi-squared tests used to test for any difference; segmented regression analysis was used to determine changes in longitudinal trend.ResultsObservations were made at 15 pre- and 15 post-ePA implementation time-points. Pre-ePA on paper, there were 18 medication administration errors in 428 opportunities for error (4.2%; 95% confidence interval 2.3–6.1%), and with ePA there were 18 in 528 (3.4%; 95% confidence interval 1.9–5.0%; p = 0.64). Regarding documentation, pre-ePA on paper there were 5 discrepancies in 460 observed documentations (1.1%; 95% confidence interval 0.1–2.0%); with ePA there were 18 in 557 (3.2%; 95% confidence interval 1.8–4.7%; p = 0.04). The most common electronic documentation discrepancy was documentation that a dose had been administered when it had not. Segmented regression analysis was unable to detect any significant longitudinal changes. Changes to working practices post-ePA were observed, such as nurses demonstrating less-consistent self-checking when preparing and administering medications.ConclusionsFindings suggest no change in medication error rate, alth